The Frequency of Anxiety and Depression in Patients with Hepatitis C at a Public Sector Liver Centre in Pakistan - Mujtaba Haider, Mujtaba Haider; Ahsan Tariq, Ahsan Tariq; Sumeen Khalid, Sumeen Khalid; Ali Sufiyan, Ali Sufiyan (Students’ Supplement of Journal of Rawalpindi Medical College, 2019)
Background: Co-morbid anxiety and depression are associated with hepatitis C. Comorbid depression is associated with increased medical symptom burden, poor quality of life and poor adherence to self-care regimens. However, in Pakistan, the data assessing the psychiatric aspect of Hepatitis C is limited. Objective: The objective of this study was to evaluate the frequency of anxiety and depression in patients with Hepatitis C at a public sector liver centre in Pakistan. Methods: Participants who were positive for hepatitis C were selected by non-probability convenience sampling. Informed consent was taken verbally and a questionnaire-based interview was implied. The questionnaire scored anxiety and depression on a verified Urdu translated version of Hospital Anxiety and Depression Scale (HADS). Data was analysed with SPSS v. 22. Results: Out of 146 participants 40% were males and 60% were females with an average age of 47.2 years. Anxiety and depression were present in 47.9% and 41.8% patients of hepatitis C respectively. There was a significant association of drug use with anxiety (p=0.01) and depression (p=0.03). Urban residency was significantly associated with anxiety (p=0.04). On comparing means it was found that women had a higher average anxiety score compared to the males (10.2 ± 4.6 vs. 9.5 ± 4.6) while males had a higher average depression score compared with females (9.8 ± 4.3 vs. 9.3 ± 4.5). However, the correlation between gender and HADS scores was not significant. Conclusion: There is a high frequency of anxiety and depression among hepatitis C patients thus regular psychiatric screening, referral, treatment and follow-up is recommended. Key Words: Anxiety, Depression, Hepatitis C, Hospital Anxiety, Depression Scale